Changing Perceptions of Marriage and Family Life Among Millennials - Karna, Wioleta; Stefaniuk, Ireneusz; Saadati, Nadereh (Journal of Psychosociological Research in Family and Culture, 2023)
Objective: The objective of this study is to explore the changing perceptions of marriage and family life among millennials. It aims to understand the factors influencing these shifts and to provide insights into the implications for future societal trends. Methods: This qualitative study employs semi-structured interviews to gather in-depth insights from a diverse group of 23 millennials, aged 25 to 40 years. Participants were selected through purposive sampling to ensure varied socioeconomic backgrounds, education levels, and relationship statuses. Data were analyzed using NVivo software through thematic analysis, with theoretical saturation guiding the data collection process. Ethical considerations included informed consent and anonymity of participants. Results: The study reveals that millennials have a pragmatic approach to marriage, viewing it as optional and prioritizing personal growth and financial stability. They favor egalitarian partnerships and accept diverse family structures, including cohabitation and single parenting. Influences from family, media, and cultural norms shape their attitudes, while economic considerations and work-life balance are significant concerns. The findings highlight a blend of traditional values and modern attitudes, reflecting broader societal changes. Conclusion: Millennials’ perceptions of marriage and family life are shaped by a confluence of factors, including evolving societal norms, economic conditions, and cultural influences. These shifts suggest a move towards individualism, equality, and flexibility in relationships and family structures. Understanding these trends is crucial for policymakers, educators, and social scientists to support millennials in achieving their personal and familial aspirations.